Inhalable curcumin formulations by supercritical technology - Kurniawansyah, F.; Mammucari, R.; Foster, Neil (Elsevier, 2015)
Inhalable dry formulations for pulmonary delivery of curcumin have been produced by supercritical antisolvent micronization. The antioxidant curcumin was co-processed with hydroxypropyl-beta-cyclodextrin (HP-ß-CD) and polyvinylpyrrolidone (PVP) to form binary and ternary composites with enhanced flow-ability for pulmonary delivery. The micronization process adopted was the atomized rapid injection solvent extraction (ARISE) system, and was operated at 95 bar and at temperatures of 25 °C and 40 °C. The products were evaluated in terms of morphology, composition, crystallinity and aerodynamic particle size distributions. A synergistic effect of the excipients on the aerodynamic properties of micronized curcumin formulations has been found. The fine particle fraction (FPF) of curcumin in ARISE-processed powders was as high as 61% in ternary systems, whilst untreated curcumin had a FPF of 10% and micronized binary systems had FPF below 40%. The process produced yields of about 80%, demonstrating significant potential for further development of curcumin formulations for pulmonary administration.